How local are labour markets? Evidence from a spatial job search model - Manning, Alan; Petrongolo, Barbara (London, 2011)
"This paper uses data on very small UK geographies to investigate the effective size of local labour markets. Our approach treats geographic space as continuous, as opposed to a collection of nonoverlapping administrative units, thus avoiding problems of mismeasurement of local labour markets encountered in previous work. We develop a theory of job search across space that allows us to estimate a matching process with a very large number of areas. Estimates of this model show that the cost of distance is relatively high - the utility of being offered a job decays at exponential rate around 0.3 with distance (in km) to the job - so that labour markets are indeed quite ‘local’. Also, workers are discouraged from applying to jobs in areas where they expect relatively strong competition from other jobseekers. The estimated model replicates fairly accurately actual commuting patterns across neighbourhoods, although it tends to underpredict the proportion of individuals who live and work in the same ward. Finally, we find that, despite the fact that labour markets are relatively ‘local’, local development policies are fairly ineffective in raising the local unemployment outflow, because labour markets overlap, and the associated ripple effects in applications largely dilute the impact of local stimulus across space."